Change of Mechanism with a Change of Substituents for a Zincke Reaction - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Almodovar-Fajardo, I; Ponce-Hormazabal, I; Onate, R (Elsevier Ltd, 2014)
The reaction between N-(2,4-dinitrophenyl)-4-(4-pyridyl)pyridinium chloride and 4-aminothiophenol led to an unexpected displacement of the 2,4-dinitrophenyl group, in contrast with the normal Zincke product formed with other nucleophilic 4-substituted anilines. Evidence for a SET process was obtained from EPR spectra of the reaction mixture. © 2014 Elsevier Ltd. All rights reserved.